THE CYBORG AUTHOR AND THE LIMITS OF TEXTUAL EXPLORATION IN THE WATER SELLER (MAI RUWA) - Riza, Haikal; Alung (Universitas Islam Negeri Sunan Gunung Djati, 2025)
Reader or user interaction is one of the main attractions of Cyber Literature. Cyber literature allows its readers to be involved in shaping the story or altering the plot within a narrative. This is made possible by the development of Hypertext technology in cyber literary works. Hypertext enables user and reader involvement within the text of a literary work. This study uses the theory of hypertext and the cyborg author by Espen J. Aarseth. The theory is used to understand how users and readers operate within cyber texts and to comprehend the function of hypertext in cyber literature. The work The Water Seller (Mai Ruwa) (2023) by Faith Bassey and Deena Larsen serves as the material object of this research. The study finds that the use of hypertext in The Water Seller (Mai Ruwa) appears merely as an attachment and does not provide an active interactive experience for the reader (user). As a result, the interaction of the cyborg author with the work is limited, resembling the interpretation of conventional literary texts.